PREPARATION, SOLID STATE CHARACTERISATION OF PACLITAXEL AND NARINGEN COCRYSTALS WITH IMPROVED SOLUBILITY - S., Muddukrishna B.; Dengale, Swapnil J.; Shenoy, Gautham G.; Bhat, Krishnamurthy (International Journal of Applied Pharmaceutics, 2016)
Objective: The objective of the present study is to prepare a better form of paclitaxel cocrystal with improved solubility. Paclitaxel (PTX) is a class-4 drug; this drug has low aqueous solubility and high affinity for P-gp. Available formulation are IV based and using our research work with advantages of co-crystal technology towards the enhancement of paclitaxel solubility and thereby its bioavailability (1) and also to improve the patient compliance. Methods: Naringen was selected based on their chemical nature and its ability to inhibit P-gp, solvent assisted grinding method used to prepare the cocrystals, and prepared cocrystals were subjected to solid state characterization to determine the crystal structure of the cocrystals, as this can provide significant new insights into how the drug and coformer interact, and thereby provide an excellent crystal engineering guide to new cocrystals, potentially with improved properties. Instruments like Fourier transform infrared spectroscopy(FTIR), differential scanning calorimetry, X-ray powder diffraction will be used to determine their stability and any phase transformations (including decomposition) which they might undergo as a function of temperature. Results: Principle involved in the formation of cocrystal is hydrogen bonding between C=O and N-H group of drug and COOH groups of coformers, which is confirmed by FTIR data and DSC experiments were carried out to study the melting point and heat of enthalpy of the cocrystals. Results clearly shows that the melting point of the cocrystals was increased which confirms the formation of cocrystals. The drug and formation of cocrystals are explained by the X-ray powder diffraction patterns. The PXRD patterns of the pure drug showed sharp, well-defined peaks(spectrum attached) and cocrystals PXRD patterns shows that there is a significant difference in the entire diffraction pattern, changes in peak locations with respect to pure drug indicates a change in the arrangement of molecules, hence confirms the development of new crystalline phase. Conclusion: The results obtained from the above experiments clearly shows the formation of cocrystals with improved solubility.